Behavioural and emotional disorders in children during COVID-19 pandemic in Ujjain district - Jain, Ritika; Dhaneria, Mamta; Srivastava , Shreya (International Journal of Contemporary Pediatrics, 2023)
Background: Objectives of the study was to find the prevalence of behavioral and emotional disorder in children and correlate it with various epidemiological factors. Methods: This observational study includes 240 children of 6 to 18 years of age using child behavioral checklist (CBCL). The study was conducted from the month December 2020 to June 2022, as this was the period with major COVID-19 cases in Ujjain district. Results: Out of 240, children showed clinically significant behavioral problems were oppositional defiant disorder 29.4% (n=5), anxiety 14.90% (n=10), attention deficit/ hyperactivity 14.9% (n=4), depression 10.421% (n=25), somatic 5.80% (n=9) and conduct problems 3.8% (n=6). Conclusions: The COVID-19 pandemic has caused behavioral problems in adolescents, correlated with age, gender, history of infection, death, and quarantine in the family member.